Study the Effect of Inductor and Pole Geometry on the Surface Roughness and Material Removal Weight Using Magnetic Abrasive Finishing Method - Mahdi, Basma Luay; Kadhum, Ali H. (Al-Nahrain Journal for Engineering Sciences, 2021)
The traditional finishing method cannot keep up with recent labor market requirements, solve the problem of increasing production, improve the surface roughness and accuracy of workpiece. While the unconventional magnetic abrasive finishing (MAF) method has shown as a promising technique that can be used to finish complicated surfaces. MAF finishes metals, alloy, ceramic, and other materials that are difficult to finish by other processes. In another word, MAF improves the quality of surfaces with low cost.This paper focuses on optimize and study the effect of inductor and pole geometry (radius of hole, angle of core, angle of pole, radius of pole), on (surface roughness (Ra) and material removal weight (W)) and fined the optimum values that increase the efficiency of MAF method. Taguchi method employed to study the influence of geometry parameters and find the optimum values using orthogonal array L9. The results conclude that the most significant factor that effects change in surface roughness (?Ra) and material removal weight(?W) are radius of the hole (R) and angle of core (?), respectively.